واقع الخدمة الاجتماعية الطبية في الجزائر - بن فرج, بختة (جامعة الوادي - University of Eloued, 2017)
الخدمة الاجتماعية كمهنة بمعناها الحديث وليدة القرن العشرين إلا ان الخدمات الاجتماعية ذاتها لازمت الإنسان منذ القدم, وكان ظهورها كمهنة متخصصة نتيجة لتجارب عديدة وجهود متواصلة في مواجهة المشكلات الإنسانية والتغيرات السريعة التي صاحبت الثورة الصناعية وتعقد الحياة الاجتماعية والضغوطات المتزايدة من بطالة وفقر وسوء الظروف المعيشية والأمراض باختلافها. والمجتمع الجزائري كغيره من المجتمعات لا يخلو من هذه الظواهر التي تعيق تطوره, وهذا استوجب الاهتمام بمختلف مجالات الخدمة الاجتماعية . وفي هذا الإطار جاءت هذه الورقة البحثية تهدف الى محاولة التطرق لمجال هام من مجالات الخدمة الاجتماعية الا وهو الخدمة الاجتماعية الطبية من خلال التعرض الى مفهومها خصائصها أهدافها أهميتها و و واقعها في الجزائر وغيرها من العناصر المهمة. Absract: Social service it self as a profession in the modern sense born of the twentieth century, but the social services them selves have long since man, and its emergence as a specialized profession as a result of many experiences and continuous efforts in the face of human problems and rapid changes that accompanied the industrial revolution and the complexity of social life and the increasing pressures of unemployment and poverty and poor living conditions and different diseases . Algerian society, like other societies, is not devoid of these phenomena that hinder its development. This necessitates attention to various areas of social service. In this context, this paper aims at trying to address an important field of social service, namely, the social medical service through exposure to its concept, characteristics, objectives, importance and reality in Algeria and other important elements. Keywords: Social service - Social medical service - Social medical service in Algeria
مقال
Keywords: الخدمة الاجتماعية- الخدمة الاجتماعية الطبية-الخدمة الاجتماعية الطبية في الجزائر